Structured education programme for women with polycystic ovary syndrome: a randomised controlled trial. Issue 1 (January 2018) - Mani, Hamidreza; Chudasama, Yogini; Hadjiconstantinou, Michelle; Bodicoat, Danielle H; Edwardson, Charlotte; Levy, Miles J; Gray, Laura J; Barnett, Janette; Daly, Heather; Howlett, Trevor A; Khunti, Kamlesh; Davies, Melanie J
Abstract : Objective: To evaluate the effectiveness of a structured education programmes in women with polycystic ovary syndrome (PCOS). Methods: Single-centre, randomised controlled trial, testing a single exposure to a group-based, face-to-face, structured education programme. Inclusion criteria were women with PCOS, aged 18–49 years inclusive and body mass index ≥23 kg/m 2 for black and minority ethnicities or ≥25 kg/m 2 for white Europeans. Primary outcome was step-count/day at 12 months. Secondary outcomes included indices of physical activity, cardiovascular risk factors, quality of life (QoL) and illness perception (IP). Results: 161 women were included (78 control, 83 intervention); 69% white; mean age 33.4 (s.d. 7.6) years, of whom 100 (48 intervention; 52 control) attended their 12-month visit (38% attrition). 77% of the intervention arm attended the education programme. No significant change in step-count was observed at 12 months (mean difference: +351 steps/day (95% confidence interval −481, +1183); P  = 0.40). No differences were found in biochemical or anthropometric outcomes. The education programme improved participants' IP in 2 dimensions: understanding their PCOS ( P  < 0.001) and sense of control ( P  < 0.01) and improved QoL in 3 dimensions: emotions ( P  < 0.05), fertility ( P  < 0.05), weight ( P  < 0.01) and general mental well-being ( P  < 0.01). Discussion: A single exposure to structured education programme did not increase physical activity or improve biochemical markers in overweight and obese women with PCOS. However, providing a structured education in parallel to routine medical treatment can be beneficial for participants' understanding of their condition, reducing their anxiety and improving their QoL.